199k views
3 votes
Heo started to solve the quadratic equation (x + 2)2 – 9 = –5. He added 9 to both sides and the resulting equation was (x + 2)2 = 4. Next, he took the square root of each side. Which was the resulting equation of that step?

1 Answer

3 votes

Explanation:

After taking the square root:

x + 2 = ±2

Notice that x + 2 can also equal -2, because (-2)² = 4.

User Jesper
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.